Merumuskan Etika Politik Kristen dalam Era Gangguan Terorisme di Indonesia - Paulus Eko Kristianto (Sekolah Tinggi Teologi Intheos Surakarta, 2019)
Abstract. Disruption of terrorism was a serious thing that threatens the life of nationalism in Indonesia. This disorder must be responded quickly and precisely as soon as possible. This article aimed to formulate one of the steps that could be taken, namely by building relevant Christian political ethics. The method used was descriptive analysis of various related literature that addresses this theme. In conclusion, Christian political ethics that have to be practiced by Christians is to develop an open understanding of